Talent Culture’s Role in Talent Development among Academics: Insights from Malaysian Government Linked Universities - Dass Mohan, Mohan; Muthaly, Siva; Annakis, John (The journal of contemporary issues in business and government, 2015)
Purpose – The purpose of this paper is to investigate the talent development antecedents in Malaysian Government Linked Companies (GLCs) Universities. Four key constructs were identified and analysed from the literature including talent identification, talent culture, competencies and talent development. Design/methodology/approach – The data required for this research were collected using a survey and online surveys sent to the three universities who participated in the study. A questionnaire was developed with 26 items adapted from previously validated scales. A non-probabilistic sampling procedure, i.e. convenience sampling, was utilised owing to the unavailability of a satisfactory sampling frame. Questionnaires were distributed to academics from three GLCs— Universiti Tenaga Malaysia (UNITEN), Universiti Teknologi Petronas (UTP) and Multimedia University of Malaysia (MMU). A total of 300 questionnaires were submitted to the GLC universities, of which 168 surveys were completed and deemed useable for data processing. Findings – The research findings revealed that talent culture plays a significant mediating role in talent identification and competencies towards talent development in retaining competent academics in Malaysian GLCs universities. The findings also suggest that in order to attract and retain competent academics, GLC universities should institute formal career development opportunities and career orientated strategic plans. Finally, public policy makers should utilise key indicators of talent identification and talent culture such as equitable performance rating systems and rewarding of exemplary contributions in order to stimulate overall talent development. Research limitations/implications – GLC universities should cultivate a Talent Management culture to enhance their talent culture and thereby increase the skills of academics and retain quality academic staff. This research highlights the potential benefits of cultivating a Talent Management culture. The results of this study will benefit the GLC universities specifically, and other educational institutions in general by assisting them to identify, develop and retain competent academics. Originality/value – This is one of the few studies that uses partial least squares to address a multifaceted problem associated with the talent management competency in Malaysian Government Linked Companies universities.